Thực trạng phát triển năng lực giáo dục STEM cho sinh viên ngành Giáo dục tiểu học: Nghiên cứu tại một số trường đại học - Ngô, Thị Liên; Nguyễn, Văn Đệ (Tạp chí Giáo dục, 2025)
In the context of general education innovation towards developing learners' qualities and competences, STEM education (Science, Technology, Engineering and Mathematics) plays an increasingly important role in primary education programs. Integrating STEM education not only helps students develop critical thinking, problem solving and creativity, but also contributes to linking knowledge with real life. Therefore, STEM education competence is an essential competency for teachers to implement STEM education. This study presents the results of a survey on the current status of STEM education capacity development for primary education students at a number of universities. The results show that the STEM education competence of primary education students is currently not being properly developed in training programs at a number of universities. Of the four components of capacity, only one competency is focused on developing at a regular level, the remaining capacities are all at the level of not being implemented or very rarely implemented. This result will be an important basis for finding solutions to develop STEM education competency for students majoring in primary education.